A New Paradigm of Open Innovation under Chinese Modernization: Co-innovation Theory Review - Zhou Guichuan; Dong Hui; Hoongsengpha Soudthida; He Yue; Zheng Shuangyi; Liu Anni (E3S Web of Conferences, 2023)
Co-innovation is a new paradigm and a new hot spot in the field of technological innovation. This study uses bibliometric analysis and CiteSpace to analyze the co-innovation related literature published at domestic and abroad during 2010-2022 to explore the current status and development trend of co-innovation research. The research results show that co-innovation research at domestic and abroad is developing rapidly and increasingly becoming a research hotspot in the field of technological innovation. Compared with foreign scholars who have begun to quantify and case study the technological paths of co-innovation, domestic research still mainly relies on qualitative methods to theoretically explore the institutional mechanism of co-innovation, which can hardly meet the development needs of co-innovation policy and practice. Therefore, this study proposes future research directions for co-innovation in four major aspects: mechanism of action, network model, empowerment mechanism and governance mechanism. As the first systematic study of co-innovation literature in China and abroad, this study has important theoretical significance and practical value.